Measurement of Tax Progressivity: Reply - Suits, Daniel B. (American Economic Review, 1980)
Two quite different issues are raised by the comments of David Davies and Edward Kienzle. The first, raised by both authors, is that use of S (or, for that matter, any other index of tax progressivity) in no way avoids fundamental problems of tax shifting, questions of how income should be measured for proper assessment of tax burden, or how to treat the difference between the distribution of lifetime tax burden compared to what is observed in any given year. The second issue, raised by Davies, deals with the validity of the index S, itself. Estimates of tax incidence differ with the kind of assumptions made about tax shifting. In this regard, the greatest variation occurs among estimates of the distribution of the burden of taxes on property, including the corporate income tax. Kienzle demonstrates this in an interesting way in his Table 2. Whether variant Ic or 3b is employed makes little difference in the value of S calculated for income, sales, or payroll taxes, but taxes on property appear highly progressive under Ic, and virtually proportional under 3b. Davies makes a similar point in noting that the value of S will depend on how income is measured. It would be interesting to see what difference would be produced if the adjustments to income he suggests were made. Likewise, it would be useful to see what happens to S when both income and tax burden are estimated on a lifetime basis. I have made a few attempts to make such calculations, but have so far been defeated by the problems of keeping track of who the taxpayer is, especially with the occurrence of divorce, widowhood, and remarriage. Davies also raises questions about the validity of S itself. His first objection-that no single index can summarize all aspects of a complicated phenomenon-largely duplicates what I said in the original presentation. The limitation is common to all averages and indexes (think of the divergence of individual price behavior concealed in movements of the Consumer Price Index) but we still find them useful. In his concluding remarks, Davies comes close to saying that tax incidence is too complex to permit tax progressivity to be measured at all. If this were true, of course, neither S nor any other such index would make sense. Personally, however, I think some useful things can be said about the relationship of tax burden to income, and that S serves as a good summary measure of those thinvs.